Quality Assessment of Shrimp (Macrobrachium rosenbergii. De Man, 1879) During Storage in Ice (Bangladesh Journal of Scientific and Industrial Research, 2012)
With a view to get a pen picture about the trend and extent of quality changes and as well as shelf life of the head off and head on shrimp (Macrobrachium rosenbergii, De Man, 1879), the present study have been carried out . Quality changes have been measured by application of sensory score evaluation and changes in chemical indices such as Total Volatile Nitrogen (TVN) value, pH and level of moisture at different time interval and Total Bacterial Count (TBC) at 15°C during the study period. The results of the sensory score evaluation indicates that the shrimp quality decreased to the limits of acceptability at 12th days of ice storage. The head off shrimp kept slight better than corresponding head on shrimps. The bacterial counts determined at 15°C have been found to increase from 103 - 107 and 104 -108 cfu/gm for head off and head on shrimp respectively at the limit of acceptability. The moisture level increased from initial 78.85gm% to final 83.80gm% (head off) & 79.0gm% to 84.0gm% (head on) and pH value increases from 7.1 to 8.1 during the whole period of iced preservation . Both head off and head on shrimp remained in acceptable condition for up to 12 and 14 days of storage respectively while the quality of fish deteriorates and become unacceptable. The bacterial count corresponding to unacceptable condition ranges from 108-109 cfu/gm fish sample. The TVN value corresponding to rejection condition were 45-50mg N/100gm fish sample. DOI: http://dx.doi.org/10.3329/bjsir.v47i1.10731 Bangladesh J. Sci. Ind. Res. 47(1), 93-98, 2012